Association Between 2D- and 3D-Speckle-Tracking Longitudinal Strain and Cardiovascular Magnetic Resonance Evidence of Diffuse Myocardial Fibrosis in Heart Transplant Recipients - Sun, Wei; Shen, Xuehua; Wang, Jing; Zhu, Shuangshuang; Zhang, Yanting; Wu, Chun; Xie, Yuji; Yang, Yun; Dong, Nianguo; Wang, Guohua; Li, Yuman; Lv, Qing; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: The study aimed to 1) evaluate the association of myocardial fibrosis (MF) and myocardial strain measured by two-dimensional (2D)- and three-dimensional speckle-tracking echocardiography (3D-STE); 2) further investigate which strain parameter measured with 2D- and 3D-STE is the more robust predictor of MF in HT recipients. Methods: A total of 40 HT patients and 20 healthy controls were prospectively enrolled. Left ventricular (LV)- global longitudinal strain (GLS), global circumferential strain (GCS) and global radial strain (GRS) were measured by 2D- and 3D-STE. LV diffuse MF was defined by cardiovascular magnetic resonance (CMR)- extracellular volume fraction (ECV). Results: The HT recipients had a significantly higher native T1 and ECV than healthy controls (1043.8±34.0ms vs 999.7±19.7ms, P＜0.001; 26.6±2.7% vs 24.3±1.8%, P=0.02). The 3D- and 2D-STE-LVGLS, LVGCS were lower (p<0.005) in the HT recipients than in healthy controls. ECV showed a moderate correlation with 2D-LVGLS (r=0.53, P=0.002) and 3D-LVGLS (r=0.60, P < 0.001), but not correlated with 2D and 3D-LVGCS, LVGRS. Furthermore, 3D-LVGLS and 2D-LVGLS had a similar correlation with CMR-ECV (r=0.60 vs 0.53, P=0.670). A separate stepwise multivariate liner analysis showed that both 2D-LVGLS (β=0.39, P=0.019) and 3D-LVGLS (β=0.54, P < 0.001) were independently associated with CMR-ECV. Conclusions: CMR marker of diffuse MF was present in asymptomatic HT patients, and appeared to be associated with decreased myocardial strain by echocardiography. Both 2D- and 3D-LVGLS were independently correlated with diffuse LVMF, which may provide an alternative noninvasive tool for monitoring the development of adverse fibrotic remodeling during the follow-up of HT recipients.